2022
DOI: 10.21270/archi.v11i5.6010
|View full text |Cite
|
Sign up to set email alerts
|

Parendodontic Surgery as a Treatment Option: Case Report with One Year Follow-Up

Abstract: Endodontic treatment aims at eliminating microorganisms from root canal systems. The resistance of these microorganisms contributes for the permanence of the apical lesion, leading to the failure of treatment. The microbiological factor is pointed out as the major cause of failures after intervention. In these cases, root canal retreatment can be performed aims the re-instrumentation, cleaning, and new filling in the root canal. Also, retreatment treatment can be associated with a parendodontic surgery in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A clinical case report reported a root canal retreatment associated with apical surgery with a one-year followup in the lower central incisor region. It was shown that paraendodontic surgery is an effective and conservative treatment option concerning extractions, and when performed correctly, with the aid of good materials such as MTA, it brings satisfactory results, returning normal conditions to the periodontal tissue, as well as health and function to the teeth affected by the inflammatory process [13].…”
Section: Vol 4 Suppl 3 Year 2023mentioning
confidence: 99%
“…A clinical case report reported a root canal retreatment associated with apical surgery with a one-year followup in the lower central incisor region. It was shown that paraendodontic surgery is an effective and conservative treatment option concerning extractions, and when performed correctly, with the aid of good materials such as MTA, it brings satisfactory results, returning normal conditions to the periodontal tissue, as well as health and function to the teeth affected by the inflammatory process [13].…”
Section: Vol 4 Suppl 3 Year 2023mentioning
confidence: 99%